The Influence of Consumer Religiosity, Halal Knowledge, Brand Awareness, on Purchase Intention of Food and Beverage in Pontianak - admin, INDA YUNITA KARTIKA B12112026 (Jurnal Manajemen Update, 2017)
Muslims in Indonesia reaches approximately 80% of the total population of Indonesia. The author interested in examining the consumption awareness of food and beverage from the Muslim community in Indonesia, especially in Pontianak. Consuming halal food and beverage shows a personâ€™s commitment to the Islamic faith and its teachings. This research also explores relationships between religiosity and halal knowledge on purchase intention toward food and beverage that sold by non-Muslim in Pontianak. Halal knowledge also has mediating role. The objective of this study is to examine the influence of consumer religiosity, halal knowledge, and brand awareness on purchase intention toward food and beverage in Pontianak. This research was carried out among the Muslim respondents within Pontianak city who age 17 and above. The author used questionnaire as the main research instrument. SmartPLS 3.2.6 software used to complete the quantitative data. The first result of the research shows that there is positive effect among brand awareness and halal knowledge. The second result is brand awareness and purchase intention, also have positive effect. Third, halal knowledge and purchase intention have positive effect. Fourth, variable religiosity and halal knowledge are also having positive effect. The last, positive result was also seen in the variable religiosity and purchase intention. Â  Keyword: Religiosity, Brand Awareness, Knowledge, Purchase Intention Â